From the particular to the universal: revolution at the heart of Robert Burns’s poetics - Cameron MORIN (E-REA)
This article focuses on Robert Burns’s poetry, and argues that an inductive movement from the particular to the universal characterises a specific poetic paradigm developed by Burns that makes him a leading figure in British and European Romanticism, following Anne-Marie Thiesse’s account of late-eighteenth century aesthetics. Following an overview of Burns’s historical and philosophical context, the linguistic fields of morphophonology and Gustave Guillaume’s theory of psychomechanics are used to demonstrate several aspects and variations of this poetic movement. Finally, I link this movement to the notion of revolution, arguing that the pragmatic potency of this notion provides the endpoint of Burnsian aesthetics, and further entrenches the poet’s status as a Romantic pioneer.